Ein experimenteller Vergleich des Investitionsverhaltens ökologisch und konventionell wirtschaftender Schweinehalter in Deutschland; Investment Behavior of Organic and Conventional Pig Farmers in Germany - An Experimental Approach - Daniel Hermann; Katrin Agethen; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2015)
Die Verfasser untersuchten mit einem Investitionsexperiment, ob sich das Investitionsverhalten bei gleichbleibenden Bedingungen durch das Framing - der Beschreibung einer Investitionsmöglichkeit in die ökologische beziehungsweise konventionelle Wirtschaftsweise - verändert. Als Ergebnis war eine deutliche Investitionszurückhaltung in die jeweils nicht praktizierte Produktionsweise festzustellen. Dieses Ergebnis und weitere Ergebnisse geben einen Hinweis darauf, dass Subventionen zur Förderung der Umstellung auf den ökologischen Landbau in ihrer Wirkung zur Förderung des Ökolandbaus überschätzt werden könnten. – – Despite the economic benefits of organic farming, the conversion rates to this production method are low. The reasons for this reluctance are largely unknown. We experimentally investigate and compare the investment behavior of organic and conventional pig farmers and examine the question whether the investment behavior changes ceteris paribus due to a varying framing - different description - of an investment possibility with organic or conventional farming. Our results show that pig farmers are more reluctant to invest in the production method which they are not currently applying compared to an investment in the production method in use on their farm. Conventional, risk-averse pig farmers and farmers who holding a university degree invest later in a hog barn. The results provide some evidence for that the effect of subsidies granted to encourage the conversion to organic farming is overestimated.
Keywords: 330